Oral microbiome dysbiosis is associated with precancerous lesions and disorders of upper gastrointestinal tract: A population-based study - Sadeghi, Fatemeh; Sohrabi, Amir; Zagai, Ulrika; Andreasson, Anna; Vieth, Michael; Talley, Nicholas J.; Agréus, Lars; Ye, Weimin (American Journal of Gastroenterology, 2024)
Background and aims: Oral microbiota may contribute to the development of upper gastrointestinal (UGI) disorders. We aimed to study the association between the microbiome of saliva, subgingival and buccal mucosa, and UGI disorders, particularly precancerous lesions. We also aimed to determine which oral site might serve as the most effective biomarker for UGI disorders. Methods: In this population-based study, 388 adults underwent upper endoscopy with biopsies for histopathological analysis. UGI symptoms were assessed using a validated questionnaire and 16S rRNA gene sequencing characterized the microbiota in 380 saliva, 200 subgingival and 267 buccal mucosa samples collected during endoscopy. Results: Dysbiosis of the salivary microbiota was observed in subjects with gastroesophageal reflux symptoms (GERS) alone, as well as in those with combined conditions such as GERS and esophagitis, or esophagitis and Barrett's esophagus. Significant microbial alterations were also found in individuals with stomach disorders including H. pylori infection, chemical reactive gastritis, atrophic gastritis, and intestinal metaplasia. However, microbiota dissimilarity in subgingival and buccal mucosa samples, was associated primarily with Barrett's esophagus or gastric atrophy. Among several identified genera, Prevotella, and Fusabacterium in saliva were associated with atrophic gastritis and intestinal metaplasia. In subgingival samples, the link between Fretibacterium in Barrett's esophagus, and Fusabacterium in gastric atrophy and intestinal metaplasia are also notable. Conclusion: Dysbiosis of the saliva microbiota is linked to various UGI disorders. However, microbiota dysbiosis in subgingival and buccal mucosa sites are specifically associated with the pre-malignant conditions Barrett's esophagus and gastric atrophy. The oral microbiome, particularly in the subgingival location, might act as biomarkers for UGI cancers.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Barrett's esophagus; Gastritis; Cancer; Esophagitis; GERD; Intestinal metaplasia; Oral microbiome